Groundless, Unsanctioned, and Unviolable Beauty (Christo and Jeanne-Claude at the UniArt Gallery) - Ivanova, Rosena (Sledva : NBU Journal of Humanities and Arts, 2020)
Choices that must be made when dealing with artworks defying representation challenge the curators to rethink the exhibition space and seek new ways to tell a story within it. This text is focused on the curatorial approach to an exhibition of posters from various site-specific projects by Christo and Jeanne-Claude. The text is also about the unique character of the works themselves as depicted on the posters, about the social and political background that connects Christo and the Bulgarian audience which was subtly contextualised in the NBU exhibition building.